2015
DOI: 10.1038/gt.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis IIIB confers enhanced neonatal intracranial transduction by AAV8 but not by 5, 9 or rh10

Abstract: Sanfilippo syndrome type B (mucopolysaccharidosis IIIB, MPS IIIB) is a lysosomal storage disease resulting from deficiency of N-acetyl-glucosaminidase (NAGLU) activity. To determine the possible therapeutic utility of recombinant adeno-associated virus (rAAV) in early gene therapy-based interventions, we performed a comprehensive assessment of transduction and biodistribution profiles of four central nervous system (CNS) administered rAAV serotypes, -5, -8, -9 and -rh10. To simulate optimal earliest treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…The inconsistency with results obtained in MPS IIIA mice and dog studies may simply be because of size differences between mice, dog, and human brain, or other factors. Interestingly, viral uptake can be impacted by disease in LSD mice, likely because of changes in extracellular matrix components that can occur in the setting of altered degradative pathways 9, 10. Additionally, the success of cross-correction relies on effective secretion from transduced cells and distribution to non-transduced cells.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistency with results obtained in MPS IIIA mice and dog studies may simply be because of size differences between mice, dog, and human brain, or other factors. Interestingly, viral uptake can be impacted by disease in LSD mice, likely because of changes in extracellular matrix components that can occur in the setting of altered degradative pathways 9, 10. Additionally, the success of cross-correction relies on effective secretion from transduced cells and distribution to non-transduced cells.…”
Section: Introductionmentioning
confidence: 99%
“…Improved transduction of mouse skeletal muscle was also obtained with tyrosine mutants of AAV8 in the lungs [11] and in the skeletal muscle by AAV6 vectors [12]. In our previous studies, we compared neonatal intracranial administration of AAV5, −8, −9, and -rh10 and concluded that AAV8 was superior to AAV5, −9, and rh10 in its ability to foster robust and widespread transduction within the mucopolysaccharidosis type IIIB (MPS IIIB) brain [13,14]. Consistent with previous studies, we also showed that AAV8 expressed a preference for neurons and astrocytes when injected in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Even among AAV vectors, different virus serotypes may give various results when administered to organisms. Therefore, 4 AAV vectors bearing the NAGLU gene, derived from AAV5, AAV8, AAV9 and AAVrh10, were tested in MPS IIIB mouse model (Gilkes et al 2016 ). Following direct injection of the viruses into CNS, various parameters were assessed, including bio-distribution and efficiency of NAGLU transduction.…”
Section: Recent Studies On Animal Models Of Mps IIImentioning
confidence: 99%
“…Following direct injection of the viruses into CNS, various parameters were assessed, including bio-distribution and efficiency of NAGLU transduction. Among tested vectors, AAV8 appeared the best one for treatment of MPS IIIB (Gilkes et al 2016 ). Nevertheless, one should consider that preferences in this animal model might potentially differ from those in patients suffering from Sanfilippo disesse.…”
Section: Recent Studies On Animal Models Of Mps IIImentioning
confidence: 99%